Bibliometric Analysis Service Oriented on Counterproductive Work Behavior (CWB): Literature Review - Dina Prasetyaningrum (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Organizational change management needs to pay attention to employee involvement and leader support for change readiness. managers and supervisors are key contributors in helping employees cope with their demands and psychologically (emotional support) preparing employees to face change by minimizing counterproductive behavior in organizational change management. The method used in this study is a literature review with a bibliometric approach, PoP (Publish or Perish), then uses VOSviewer. Based on the Systematic Literature Review (SLR) Bibliometric analysis of change management in organizational change behavior, it is necessary to pay attention to the importance of emotional support, job involvement, job satisfaction, and occupational health to minimize negative counterproductive work behavior in organizations. Also reinforced by the need for and importance of social support based on Social Exchange Theory, employees who receive social support from their superiors try to reciprocate or return benefits from their superiors by showing extra effort in their work.